LEVELS OF PROFESSIONAL COMPETENCE OF ENVIRONMENTALISTS - RIDEI, Nataliia; RYBALKO, Yuliya; STROKAL, Vita (Trends in education, 2012)
The article discusses levels of professional competence of environmentalists and, the explanation of their performance to achieve good results has been revealed.
Keywords: level of competence; professional competence; environmentalist.